Participatory Rural Appraisal (Better Evaluation)
"Participatory Rural Appraisal (PRA) recently renamed Participatory Le arning for Action (PLA), is a methodological approach that is used to enable farmers to analyse their own situation and to develop a common perspective on natural resource management and agriculture at village level. PRA is an assessment and learning process that empowers farmers to create the information base they need for participatory planning a nd action. Outsiders contribute facilitation skills and external infor mation and opinions. Many different tools have been developed for use in PRA. There are four main classes: tools used in group and team dyna mics; tools for sampling; options for interviews and dialogue; and opt ions for visualisation and preparing diagrams. Most countries have had some experience with PRA and local publications are available. IIED r egularly reports on new developments in its PLA notes (Pretty et al 19 95)." (Bie, 1998)